Magnetic‐Flux‐Induced Tunable Completely Flat Band and Topological Nearly Flat Band in Square Kagome Lattice. Issue 3 (7th February 2023) - Chen, Chao; Qi, Lu; Hu, Kai‐Xin; Cao, Ji; Cui, Wen‐Xue; Zhang, Shou; Wang, Hong‐Fu
Abstract: The flat bands in a square kagome lattice containing square and triangle plaquettes, are respectively investigated, and the origin of the doubly degenerated completely flat bands and the corresponding compact localized states are elucidated. It is found that the introduction of external magnetic flux enriches the modulation parameters, making the system present many interesting results. In the case that the magnetic flux penetrates through each square plaquette, the tunable completely flat band has one more tunable parameter. And when the external magnetic flux penetrates through each triangle plaquette, excepting a completely flat band, the band dispersions of the system present the topological nearly flat band, which is very useful to realize the interesting fractional quantum Hall physics. The average density of states is also calculated to corroborate the completely FB generated by the highly localized eigenstates. Furthermore, the implementation of the square kagome lattice system based on the current photonic waveguide network technology is demonstrated. The scheme opens up a way to generate the tunable completely flat band and topological nearly flat band in square kagome lattice under multi‐parameter variable conditions. Abstract : The introduction of external magnetic flux enriches the modulation parameters, making the square kagome lattice present many interesting results. With the inclusion of magnetic flux on each square plaquette, the tunable completely flat band has one more tunable parameter. In the presence of magnetic flux penetrating through each triangle plaquette, the topological nearly flat band appears in the system.